Sistema para Evaluar el Estrés del Retículo Endoplásmico en Apis mellifera - Orozco-Lucero, Ernesto (Universidad Autonoma "Benito Juárez" de Oaxaca, 2024)
The honey bee (Apis mellifera) population suffers a worldwide decrease due to diverse stress factors, as parasitosis by Varroa destructor. Knowledge of the regulatory mechanisms underlying cell stress in A. mellifera, including endoplasmic reticulum stress (ERS), a stress pathway with pivotal importance and closely related to the unfolded protein response (UPR), is far from complete. We present here a System for Evaluating Endoplasmic Reticulum Stress in A. mellifera (SEERSAm), whose aim is to determine if varroa infestation alters ERS and its related pathways (UPR, autophagy, and apoptosis) in A. mellifera. Primers targeting ERS/UPR (grp78; atf6; ire1; eif2a; calr; Xbp1; and grp94) and autophagy (atg7) transcripts were designed and primers targeting apoptosis-related transcripts (Apaf1; bsk; casp3; casp9; iap; and buffy) were chosen from the literature. Beehives with null-low, medium, and high V. destructor infestation (according to the method of natural mite mortality) will be sampled. Total RNA from the fat body of nurse worker bees will be extracted for qPCR with the corresponding cDNA. The abundance levels of the transcripts of interest will be assessed. The SEERSAm, currently in progress, will be instrumental to know the molecular regulation of ERS and its related pathways in the fat body of A. mellifera due to V. destructor infestation.